An improved firefly algorithm for routing in flying ad hoc networks. (28th September 2021) - Yadav, Amrita; Verma, Seema
This paper presents a new and improved firefly algorithm which can be used to solve routing issues in flying ad hoc networks. A flying ad hoc network is basically a new form of mobile ad hoc network (MANET) in which multiple unmanned aerial vehicles (UAV) are connected together in the form of nodes. Routing has been a foremost issue in FANETs. Firefly algorithm (FA) is one such nature-inspired swarm intelligence algorithm which gives efficient results when compared with other conventional algorithms. The proposed approach uses clustering as the methodology. The parameters taken in this algorithm to analyse the results are packet delivery ratio, end-to-end delay, routing overhead and throughput. The results of the proposed algorithm are compared with ant colony optimisation (ACO) and existing FA. The results indicate that this algorithm is considerably better than existing firefly algorithm and ACO and can be used for finding optimal routing solutions.